2008
DOI: 10.1111/j.1365-2362.2008.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of osteopontin in patients with triple‐negative breast cancer

Abstract: Patients with osteopontin overexpression develop predominantly triple-negative tumours. Osteopontin overexpression is associated with tumour aggressiveness and poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 31 publications
(50 reference statements)
6
28
0
1
Order By: Relevance
“…We have previously demonstrated that the triplenegative phenotype of breast carcinomas is significantly associated with osteopontin (OPN) overexpression (Wang et al 2008). Additionally, studies have shown that the basal-like/triple-negative subtype is also associated with P53 overexpression (Tuck et al 1997;Turner et al 2004;Parikh et al 2008a, b).…”
Section: Discussionmentioning
confidence: 98%
“…We have previously demonstrated that the triplenegative phenotype of breast carcinomas is significantly associated with osteopontin (OPN) overexpression (Wang et al 2008). Additionally, studies have shown that the basal-like/triple-negative subtype is also associated with P53 overexpression (Tuck et al 1997;Turner et al 2004;Parikh et al 2008a, b).…”
Section: Discussionmentioning
confidence: 98%
“…The finding of higher osteopontin and ON expression in bone-metastasizing human prostate cancer tissue highlights the potential prognostic value of osteopontin and other bone-resident proteins in cancer [207, 208]. Osteopontin levels are also higher in triple-negative breast cancers [209]. Periostin is another secreted stromal protein overexpressed in many cancers including prostate, breast, colon, ovarian, pancreatic, and melanoma stroma.…”
Section: Secreted Proteinsmentioning
confidence: 99%
“…Wang et al [132] evaluated osteopontin protein expression in TNBC to determine if they correlated with clinicopathological parameters on 117 breast carcinoma tissue samples, and then assessed the mean value of osteopontin expression against TN-status and clinicopathological parameters. Of the 239 patients in the study, 47 were classified as triple negative.…”
Section: Altered Expression Of Several Oncogenic Proteins and Tumomentioning
confidence: 99%